Metode Penelitian Dalam Studi Islam Melalui Pendekatan Normatif, Historis dan Filosofis - Badrut Tamam; Muhammad Irhas Rasuli; Eko Nursalim (STIT Syekh Muhammad Nafis Tabalong, 2025)
Islamic studies as a scientific discipline continues to experience methodological developments in line with the increasing complexity of religious and social issues in the contemporary era. The study of Islam is no longer sufficient through a single approach, but requires the integration of normative, historical, and philosophical perspectives to fully understand Islam, both as a normative teaching and as a social and intellectual reality. This article aims to analyze the concepts, characteristics, and relevance of integrating these three approaches in developing a modern Islamic studies methodology. This research uses library research with a qualitative approach and content analysis of various classical and contemporary literature relevant to Islamic research methodology. The results of the study indicate that the normative approach serves to maintain the purity of Islamic teaching sources and moral direction; the historical approach enriches the social context and evolution of Islamic thought; while the philosophical approach deepens epistemological, ontological, and axiological reflection. The integration of these three produces a methodological framework that is scientific, contextual, and responsive to contemporary issues such as digital fiqh, religious moderation, and modern Islamic education. This article contributes to strengthening an integrative methodological paradigm relevant to the development of Islamic studies curricula, educational practices, and interdisciplinary research in the modern era.